2018
DOI: 10.1136/bcr-2018-224471
|View full text |Cite
|
Sign up to set email alerts
|

A misplaced peripherally inserted central catheter presenting as contralateral pleural effusion

Abstract: A preterm neonate born at 27 weeks, with a birth weight of 555 g, was on continuous positive airway pressure (CPAP) for apnoea of prematurity and initially received total parenteral nutrition (TPN) through the umbilical venous catheter. Peripherally inserted central catheter (PICC) was inserted in the left basilica vein on day 8 to continue TPN. The baby developed respiratory distress with persistent hypoxia after TPN was initiated through the PICC line. The baby required mechanical ventilation due to worsenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In summary, a non-central tip position was more likely to result in complications and non-selective ECC removal (6, 13). Limb movement, neck position, forceful flushing, and neonatal growth during insertion and the dwell period may change the tip position of a peripherally inserted central catheter (PICC) line (3,5). Despite best efforts, catheter tips may not start or stay in a central location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, a non-central tip position was more likely to result in complications and non-selective ECC removal (6, 13). Limb movement, neck position, forceful flushing, and neonatal growth during insertion and the dwell period may change the tip position of a peripherally inserted central catheter (PICC) line (3,5). Despite best efforts, catheter tips may not start or stay in a central location.…”
Section: Discussionmentioning
confidence: 99%
“…Extravasation of PN into the pleural space can cause serious pleural effusion (PE). ECC-related PE can cause acute respiratory distress and may be life-threatening without timely diagnosis and adequate interventions (1)(2)(3)(4)(5). Early identification and correct treatment are necessary to improve the prognosis of this devastating complication.…”
Section: Introductionmentioning
confidence: 99%
“…There have been only a few cases (more in neonates than adults) of TPN-related pleural effusion as a complication after PICC placement. 15,16 In our situation, despite in working order, the PICC could have caused micro-trauma to the smaller subclavian and brachiocephalic veins leading to erosion. 17 In addition, having hyperosmolar fluid such as TPN infused with a pump can lead to breakdown of the endothelium further leading to seepage of TPN into the pleural spaces.…”
Section: Discussionmentioning
confidence: 73%
“…They took a sitting position, leaned their body forward 45° and extended their shoulder joint to the maximum angle in order to move the tip of the catheter up. 12,13 The authors performed a jet injection of 0.9% Saline and checked the result using the intracavitary electrocardiography method of tip location. [14][15][16][17][18] After the appearance of high-amplitude P waves, chest radiograph showed that the PICC was re-positioned into the vena cava in five cases.…”
Section: Management Of Secondary Malposition Of Picc Into Azygos Veinsmentioning
confidence: 99%